Health condition and mycobiome diversity in Mediterranean tree species - Diez-Hermano, Sergio; Ahmad, Farooq; Niño-Sanchez, Jonatan; Benito, Alvaro; Hidalgo, Elena; Escudero, Laura Morejón; Morel, Wilson Acosta; Diez, Julio Javier (Frontiers in Forests and Global Change, 2022)
Introduction Mediterranean forests are currently facing a surge in abiotic stressors such as droughts and massive fires as a result of climate crisis and human pressure. Susceptibility to biotic stressors has also increased, including a variety of pests and pathogens capable of weakening and potentially killing forest flora. Biodiversity of microbiome protects forests against declines as it increases trees’ resilience and adaptability. Objectives With the objective of analyzing the relationship between health status and fungal diversity, in the present work the mycobiota of declined and healthy specimens of keystone Mediterranean tree species is described and compared. Methods To this end, bark and wood from declining Spanish forests of Castanea sativa (chestnut), Quercus ilex (holm oak), Quercus suber (cork oak), and Quercus pyrenaica (pyrenean oak) were sampled and the Internal Transcribed Spacer (ITS1) genomic region was sequenced. Results Results showed a predominance of Ascomycota, Basidiomycota, and Mucoromycota in all samples. Alpha diversity at genus level was not affected by health status and was characterized by uneven, poorly distributed fungal communities dominated by a few genera. Differentially abundant (DA) genera between healthy and declined samples were found in chestnut (15), holm oak (6), and pyrenean oak (4) trees, but not in cork oak. Some genera known for their plant protection potential, such as Trichoderma, were found exclusively in healthy trees. Functional profiles revealed a predominance of phytopathogens and saprobes in all tree species, irrespective of their health status. Discussion This study emphasizes the importance of Mediterranean forests as biodiversity refuges and highlights the value of above-ground tissues as a valid approach to assess shifts in forests’ microbiome diversity in response to biotic and abiotic stressors.